Aplikasi Administrasi Penjualan Dengan Menggunakan Vb.Net 2022 - Yunita Sari; Eka Rini Yulia (IMTechno: Journal of Industrial Management and Technology, 2023)
- The system of selling goods at the cashier still uses a method that is not yet computerized. This is very unfortunate because it does not take advantage of the technological system that is currently growing. Information technology that uses a computerized system in recording sales can be very useful, and in accordance with actual sales data, so there is little possibility of price manipulation and stock availability. This can also be used so that employees are better at processing sales transactions, which are currently only recorded in the register book or a sales ledger, and the stock of goods is recorded manually in the stock book. In addition, there is no proper recording of customer data, so that if the store wants to hold a sales promotion, it is difficult to contact customers. The design of the sales administration application program at Nad House Bakery can help staff who serve as cashiers in recording customer data, data on goods sold to sales transactions. So that sales reports do not need to be made or calculated manually. So besides including time efficiency, it can also be efficient for storage. Sales reports can also produce more precise data because they are stored in the database during the sales process